3D hybrid porous Mxene-sponge network and its application in piezoresistive sensor. (August 2018) - Yue, Yang; Liu, Nishuang; Liu, Weijie; Li, Mian; Ma, Yanan; Luo, Cheng; Wang, Siliang; Rao, Jiangyu; Hu, Xiaokang; Su, Jun; Zhang, Zhi; Huang, Qing; et al.
Abstract: High-performance pressure sensors attract widespread attention due to the potential applications in human-machine interaction and wearable electronics. However, most of flexible pressure sensors need elaborate nanostructure design, and thus their manufacture is consuming and complicated. Therefore, a large-scale and low-cost technology is highly desirable to fabricate flexible pressure sensitive materials with high sensitivity in broad pressure range. Here, an MXene-sponge was fabricated by a simple and efficient dipping-coating process method and was applied in the piezoresistive sensor with insulating Polyvinyl Alcohol (PVA) nanowires as a spacer. The sensor based on MXene-sponge presents high sensitivity for a broad pressure range (147 kPa −1 for less than 5.37 kPa region and 442 kPa −1 for 5.37–18.56 kPa region), a low detection limit of 9 Pa, a rapid response time of 138 ms, and an excellent durability over 10, 000 cycles. Human physiological signal (such as respiration, joint movement and pulses) can be real-time monitored by the MXene-sponge sensor. The potential applications of the sensor in measuring pressure distribution and human-machine interaction are also explored. Graphical abstract: fx1 Highlights: MXene-sponge hybrid structure has excellent pressure sensing performances. 2D MXene can be easily assembled into devices by one-step dipping-drying method. The MXene-sponge/PVA NWs based sensor presents a high sensitivity of 442 kPa −1 .